Operation of calcium-birnessite water-oxidation anodes: interactions of the catalyst with phosphate buffer anions. Issue 21 (1st October 2021) - Ronge, Emanuel; Ohms, Jonas; Roddatis, Vladimir; Jones, Travis; Sulzmann, Frederic; Knop-Gericke, Axel; Schlögl, Robert; Kurz, Philipp; Jooss, Christian; Skorupska, Katarzyna
Abstract : Interactions of the calcium-birnessite catalyst with phosphate buffer anions under water-oxidation conditions. Abstract : Investigating the interfaces between electrolytes and electrocatalysts during electrochemical water oxidation is of great importance for an understanding of the factors influencing catalytic activity and stability. Here, the interaction of a well-established, nanocrystalline and mesoporous Ca-birnessite catalyst material (initial composition K0.2 Ca0.21 MnO2.21 ·1.4H2 O, initial Mn-oxidation state ∼+3.8) with an aqueous potassium phosphate buffer electrolyte at pH 7 was studied mainly by using various electron microscopy and X-ray spectroscopy techniques. In comparison to electrolyte solutions not containing phosphate, the investigated Ca-birnessite electrodes show especially high and stable oxygen evolution activity in phosphate buffer. During electrolysis, partial ion substitutions of Ca 2+ by K + and OH − /O 2− by H n PO4 (3− n )− were observed, leading to the formation of a stable, partially disordered Ca–K–Mn–H n PO4 –H2 O layer on the outer and the pore surfaces of the active electrocatalyst material. In this surface layer, Mn 3+ ions are stabilized, which are often assumed to be of key importance for oxygen evolution catalysis. Furthermore, evidence for the formation of [Ca/PO4 /H2 O] − complexes located between the [MnO6 ] layers of the birnessite was found using the soft Ca 2p and Ca L-edge X-ray spectroscopy. A possible way to interpret the observed, obviously very favorable "special relationship" between (hydrogen)phosphates and Ca-birnessites in electrocatalytic water oxidation would be that H n PO4 (3− n )− anions are incorporated into the catalyst material where they act as stabilizing units for Mn 3+ highly active centers and also as "internal bases" for the protons released during the water-oxidation reaction.